Social networking GPS tracker "GETCHA" using HTML5 / Puteri Emilia Fazrin Mohd Nasir - Mohd Nasir, Puteri Emilia Fazrin (2012)
This research uses Blackberry Messenger as a platform to connect user with other user who used Blackberry device. The technique use in this research is Blackberry Enterprise Server, to connect within the device where it has Instant Messaging Server that can be used for this project. As for the GPS location, we first send radio signals to the satellite to obtain the coordinate of the current location. Later then the coordinate will send to the Google Map API server to obtain the location map. This location map will tell roughly the current position of the user. Both of this are combine to develop this application not only able to detect the user's current location but also the user's friend location. This application is fully created by HTML5, the latest Hypertext Mark up Language that have proposed in 2010.